Legal status of subjects of pledge legal relationship (Journal of actual problems of jurisprudence, 2019)
This article is sanctifi ed to legal status of subjects of mortgage legal relationship.Keywords: mortgage, the mortgaged property, the mortgagor, the mortgagee.